Inside Cover: Towards Utilising Photocrosslinking of Polydiacetylenes for the Preparation of "Stealth" Upconverting Nanoparticles (Angew. Chem. Int. Ed. 49/2018). Issue 49 (14th November 2018) - Nsubuga, Anne; Zarschler, Kristof; Sgarzi, Massimo; Graham, Bim; Stephan, Holger; Joshi, Tanmaya
Abstract : Photocrosslinkable diacetylenes were used for the biocompatibilization of upconverting nanoparticles (UCNPs). In their Communication onpage 16036 ff., T. Joshi, H. Stephan, K. Zarschler, and co‐workers demonstrate that biomolecular corona‐resistant UCNPs can be generated by first coating the UCNP surface with a mixture of diacetylenic ligands and phospholipids, followed by irradiation with UV light. These ene–yne cross‐linked bright UCNPs contain sites for linking bio/radioactive moieties.